2016
DOI: 10.4993/acrt.24.35
|View full text |Cite
|
Sign up to set email alerts
|

Circulating galectin-3 correlates with angiogenetic factors, indicators of nutritional condition and systemic inflammation in patients with thyroid cancer

Abstract: Background and Aims: Several investigators have reported the significance of circulating galectin-3 in thyroid cancer patients. However, the precise meaning of circulating galectin-3 remains unclear. The aim of this study was to investigate the relationships between serum galectin-3 levels and angiogenetic factors, and nutritional and inflammatory indicators in patients with thyroid cancer. Materials and Methods: Sixty-one patients with thyroid tumors were enrolled, comprising 47 pre-treatment thyroid cancer p… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2017
2017
2022
2022

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(2 citation statements)
references
References 36 publications
0
2
0
Order By: Relevance
“…Moreover, inflammation is thought to play a role in papillary carcinoma of the thyroid, which is characterized by the presence of chemokine-guided macrophage and dendritic cell infiltration [ 20 22 ]. However, the majority of the studies investigating serum biomarkers and thyroid carcinogenesis have focused on progression and treatment response, with little focus on the risks of developing thyroid cancer [ 6 , 8 , 23 ].…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Moreover, inflammation is thought to play a role in papillary carcinoma of the thyroid, which is characterized by the presence of chemokine-guided macrophage and dendritic cell infiltration [ 20 22 ]. However, the majority of the studies investigating serum biomarkers and thyroid carcinogenesis have focused on progression and treatment response, with little focus on the risks of developing thyroid cancer [ 6 , 8 , 23 ].…”
Section: Discussionmentioning
confidence: 99%
“…For thyroid cancer, histological studies have confirmed the infiltration of white blood cell components such as CD8+ and CD4+ regulatory T lymphocytes in cancer tissues [ 4 ]. Moreover, increased levels of positive acute phase proteins like C-reactive protein (CRP), haptoglobin, galectin-3, IL6, G-CSF, sICAM-1, high neutrophil-to-lymphocyte ratio (NLR) and decreased levels of negative acute phase proteins like albumin, pre-albumin, and transferrin have been found in sera of patients with thyroid cancers [ 5 8 ]. Epidemiological studies have also suggested a link between chronic inflammation and risk factors for developing a thyroid cancer such as radiation exposure during childhood or as an occupational hazard [ 9 ], downstream genetic mechanisms in familial thyroid cancer syndromes [ 10 ], Hashimoto’s Thyroiditis [ 11 ], obesity [ 12 ], Hepatitis C-related chronic hepatitis [ 13 ] and increased parity and lactation [ 14 ].…”
Section: Introductionmentioning
confidence: 99%